2011
DOI: 10.1007/s00296-011-2308-x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombosis in Behçet’s disease: a Behçet’s disease patient with complete thrombotic obstruction of IVC and both iliac veins and decreased protein S activity

Abstract: Behçet's disease represents a multisystemic inflammatory disease characterized by recurrent oral ulcers, genital ulcers, and uveitis. Although vascular attack and thrombosis are not major complications in Behçet's disease, they can still pose risks that must not be overlooked. In this paper, we reported that a 25-year-old female Behçet's disease patient with complete thrombotic obstruction of the inferior vena cava that was successfully treated by aspiration thrombectomy and balloon angioplasty. The procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It is a rare vasculitis in sub-Saharan Africa and is more common in the Mediterranean region. Vascular thrombosis, especially venous, is common in this condition and also constitutes a basic diagnostic criterion [ 1 ]. Its affection of the superior vena cava is rather rare with only a few cases described in the literature [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is a rare vasculitis in sub-Saharan Africa and is more common in the Mediterranean region. Vascular thrombosis, especially venous, is common in this condition and also constitutes a basic diagnostic criterion [ 1 ]. Its affection of the superior vena cava is rather rare with only a few cases described in the literature [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that insufficiency or a lack of natural anticoagulant proteins, including PC, PS, and antithrombin, play a role in thrombosis among BD patients (27,28). In the present case, the prolonged PT may be related to the warfarin treatment, the elevated D-dimer may be linked to using uro-kinase, and the low activity of PC and PS may have been the cause of the thrombosis event.…”
Section: Discussionmentioning
confidence: 60%
“…Similar to SLE, these results suggest that APS may be involved in BD. In relation to thrombosis, this mechanism may also have affected the present case and other cases of patients with BD, such that an occlusion or thrombosis are accompanied by elevated aCL, LA, and anti-β2-GP1 (28,36). There is no direct evidence that steroid therapy can prevent the recurrence of thrombosis in APS patients; however, it may suppress the aPL titers.…”
Section: Discussionmentioning
confidence: 76%